Relationship between Malaysian newspaper journalists knowledge, attitude and law-ethics priority and possible ethical behavior - Motlagh, Nafise Esmael (2013)
This research is about journalism ethics in Malaysia. The main objective of this study is to determine the relationship between Malaysian newspaper journalists‟ knowledge,attitudes, law-ethics priority and their possible ethical behavior. To achieve this objective, a KAP study (Knowledge, Attitude, and Practice) was applied to reveal what Malaysian journalists know about journalism ethics; how they feel about it, and how they possibly behave in uncertain ethical situations. This study also tried to find out if journalists‟ behavior affected by their gender, journalism education and experience. The methodology of this study was based on two approaches: a quantitative survey and a few supporting interviews. Self-administered questionnaires were used as the instrument to collect the data from 231 full-time journalists. The journalists were selected from five highly-circulated newspapers by non-probability sampling (convenience).The questionnaire was divided into five sections under the following headings: 1. profile of respondents, 2. knowledge about journalism ethics, 3. attitude towards journalism ethics, 4.possible ethical behavior and 5.Law-ethicspriority. The data were analyzed by Statistical Package for Social Sciences (SPSS) version 17.0 for Windows. Descriptive statistics, Chi-square test, Pearson correlation test, independent sample t-test, normality test and multiple regression test were used to achieve the objectives. The results showed that almost half of the 231 journalists (49.8%) who participated in this study had low knowledge about journalism ethics,51.8% had unfair possible behavior in uncertain situations and58.9% of them had unfavorable attitude towards journalism ethics. It was also revealed that Malaysian journalists cared more about law rather than ethics in their profession. They consider law as obligatory and ethics as aspirational. Based on the two different schools of thinking, they were mostly into “separate realms model” which is not based on social responsibility theory. This study also found that there is a significant relationship between journalists‟ possible ethical behavior and their knowledge and attitude, but no relationship was found between their ethical behavior and law-ethics priority. In other words, the journalists‟ knowledge and attitude towards journalism ethics could make a difference in their possible ethical behavior. According to the results, work experience also played a significant role in journalists‟ possible ethical behavior. This study found attitude and work experience as two predictors which contributed most in journalists‟ possible ethical behavior. In the supporting interviews, two important concerns were mentioned by senior local journalism regarding to ethical journalism practice in Malaysia, including governmental media ownership and Asian social-religious values. The majority of interviewees believe that in order to understand the journalists‟ perception about journalism ethics and the restrictions against ethical/professional behavior the structure of media and society should be considered. They also said the media companies, the union of journalist and other related media organizations play an important role in improving the level of ethical journalism in Malaysia by conducting trainings and open discussions.